Expectations and educational needs of rheumatologists, rheumatology fellows and patients in the field of precision medicine in Canada, a quantitative cross-sectional and descriptive study - Sophie Ruel-Gagné (BMC, 2021)
Abstract Background Precision medicine, as a personalized medicine approach based on biomarkers, is a booming field. In general, physicians and patients have a positive attitude toward precision medicine, but their knowledge and experience are limited. In this study, we aimed at assessing the expectations and educational needs for precision medicine among rheumatologists, rheumatology fellows and patients with rheumatic diseases in Canada. Methods We conducted two anonymous online surveys between June and August 2018, one with rheumatologists and fellows and one with patients assessing precision medicine expectations and educational needs. Descriptive statistics were performed. Results 45 rheumatologists, 6 fellows and 277 patients answered the survey. 78% of rheumatologists and fellows and 97.1% of patients would like to receive training on precision medicine. Most rheumatologists and fellows agreed that precision medicine tests are relevant to medical practice (73.5%) with benefits such as helping to determine prognosis (58.9%), diagnosis (79.4%) and avoid treatment toxicity (61.8%). They are less convinced of their usefulness in helping to choose the most effective treatment and to improve patient adherence (23.5%). Most patients were eager to take precision medicine tests that could predict disease prognosis (92.4%), treatment response (98.1%) or drug toxicity (93.4%), but they feared potential negative impacts like loss of insurability (62.2%) and high cost of the test (57.5%). Conclusions Our study showed that rheumatologists and patients in Canada are overall interested in getting additional precision medicine education. Indeed, while convinced of the potential benefits of precision medicine tests, most physicians don’t feel confident in their abilities and consider their training insufficient to incorporate them into clinical practice.